2020
DOI: 10.3390/w12061524
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Groundwater and River Water Interconnections Using Hydrochemistry, Stable Isotopes, and Statistical Methods in Hanumante River, Kathmandu Valley, Central Nepal

Abstract: Interconnection between river water and groundwater plays an important role in maintaining water quantity and quality in hydrological systems. Furthermore, the exact interconnection is often difficult to observe and measure. This study attempts to explain river and shallow groundwater interconnection in urbanized areas of the Kathmandu Valley, Nepal. Isotopic (δD and δ18O) and chemical analyses were performed on river and groundwater samples, and the results were analyzed using statistical methods to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…A number of meat shops, hospitals, and a pharmacy were present in the surroundings (within 200 m) of the shallow wells where 8 ARGs were detected. Contamination of shallow dug wells by wastewater from such establishments and discharging of untreated wastewater and partially treated municipal, industrial, and hospital wastewaters to rivers may have affected shallow groundwater ( Mackie et al, 2006 ; Elliott et al, 2018 ; Bajracharya et al, 2020 ; Hubbard et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of meat shops, hospitals, and a pharmacy were present in the surroundings (within 200 m) of the shallow wells where 8 ARGs were detected. Contamination of shallow dug wells by wastewater from such establishments and discharging of untreated wastewater and partially treated municipal, industrial, and hospital wastewaters to rivers may have affected shallow groundwater ( Mackie et al, 2006 ; Elliott et al, 2018 ; Bajracharya et al, 2020 ; Hubbard et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…( Ghaju Shrestha et al, 2017 ), as well as human and animal fecal contamination in these water sources ( Malla et al, 2015 , 2018a , b , 2019 ). Similarly, river water, which is extensively used for irrigation of vegetable farms in the valley, is highly contaminated with pathogens ( Shrestha et al, 2017b ), and the interconnection between river water and groundwater of the Kathmandu Valley ( Bajracharya et al, 2020 ) indicates a high possibility of pathogen contamination of groundwater.…”
Section: Methodsmentioning
confidence: 99%
“…Mann Whitney test revealed significant variation (p<0.05) between the Bheri and the Babai River systems with regard to Ca 2+ , Mg 2+ , HCO 3 − and SO 4 2− (Figure 2). Ca 2+ and HCO 3 − are often the most dominant cation and anion in freshwater systems globally (Wetzel, 2001) and a large number of studies across Nepal and elsewhere have reported the dominance of these ions in different freshwater bodies (Lacoul and Freedman, 2005;Bajracharya et al, 2020;Bhatta et al, 2022). In contrast, the concentrations of K + ions were lowest in both the water bodies.…”
Section: Major Ions and Their Seasonal Variationmentioning
confidence: 99%
“…There is a significant difference in water quality entering the Valley floor from headwater catchments with natural land uses (Davids et al 2018). The shallow groundwater quality does not improve as quickly because the amount of groundwater in storage is high, and groundwater flow velocities are low, which leads to a slower rate of change (Bajracharya et al 2020). It is also possible that shallow aquifer recharge in the Valley floor is of lower quality because of extensive overlying-built land-uses.…”
Section: Impact Of Stream-aquifer Interaction In Groundwater Qualitymentioning
confidence: 99%